2009
DOI: 10.1097/mnm.0b013e32832b9aad
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive treatment of a murine melanoma using a 32P-patch

Abstract: The (32)P-patch tested for the treatment of a murine melanoma model showed its efficacy, as tumor growth was retarded after application of the patch Nevertheless, adjustment of some therapeutic parameters and/or combining the patch with other treatment modalities may be necessary to achieve complete regression. The P-patch represents a powerful tool to individualize the treatment of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In recent years, specially designed patches containing 32 P have been developed for contact brachytherapy of skin lesions. [8][9][10][11] In a previous work, the authors of the present study have reported the preliminary results on the preparation of 32 P-based skin patch to test the efficacy of 32 P in controlling tumor growth. 12 In this communication, a detailed investigation on the preparation, properties, and quality of 32 P-based skin patch has been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, specially designed patches containing 32 P have been developed for contact brachytherapy of skin lesions. [8][9][10][11] In a previous work, the authors of the present study have reported the preliminary results on the preparation of 32 P-based skin patch to test the efficacy of 32 P in controlling tumor growth. 12 In this communication, a detailed investigation on the preparation, properties, and quality of 32 P-based skin patch has been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapies include surgery and radiotherapy are considered the best therapy for keloids that do not respond to conventional therapy 3 . Salgueiro (2009) has conducted research to see whether the effects of radioisotopes as open sources can have the same effect as a sealed source 4 . In this study, 32 P solution was converted into chromic phosphate powder which was then mixed with silicon to form 32 P sheets or plaster.…”
mentioning
confidence: 99%